A pH‐Responsive Soluble‐Polymer‐Based Homogeneous Ruthenium Catalyst for Highly Efficient Asymmetric Transfer Hydrogenation (ATH). Issue 6 (9th May 2016) - Xie, Yinzheng; Wang, Mengpan; Wu, Xiaohui; Chen, Chen; Ma, Wenbo; Dong, Qifeng; Yuan, Mingming; Hou, Zhenshan
Abstract: A pH‐responsive polymer has been synthesized successfully by means of copolymerization of dimethyl aminopropyl acrylamide (DMAPA) and N ‐ p ‐styrenesulfonyl‐1, 2‐diphenylethylenediamine (V‐TsDPEN). The pH‐responsive polymer coordination ruthenium complex was thus prepared and employed as an efficient catalyst for the asymmetric transfer hydrogenation (ATH) of various ketones. The polymer catalyst exhibited an attractive pH‐induced phase‐separable behavior in water: it could be dissolved in water when the pH of the solution was lower than 6.5 at the beginning of the reaction, but was precipitated completely from water when the pH of the solution was above 8.5 after reaction. Additionally, the catalysts were highly efficient for the ATH of a wide range of substrates that bore different functional groups and could be recycled easily from the aqueous solution by means of self‐separation. They could be recycled eight times without significant changes in catalytic activity and enantioselectivity. Abstract : Catalytic converter : A pH‐responsive polymer catalyst was synthesized by the copolymerization of dimethyl aminopropyl acrylamide and N ‐ p ‐styrenesulfonyl‐1, 2‐diphenylethylenediamine, followed by coordination with Ru complexes (see figure). The catalyst was highly efficient for asymmetric transfer hydrogenation of a wide range of substrates and was recycled easily by means of pH‐induced precipitation.